La conversión como metáfora espacial: una propuesta de aproximación cognitiva al cambio cultural de la Antigüedad Tardía1 - Herrero de Jáuregui, Miguel ('Ilu. Revista de Ciencias de las Religiones, 2005)
Religious conversion is a practically non-existent notion in the Ancient World, in which it suddenly spreads out quickly with the advent of Christianity. It is constructed in spacial terms, as a process of movement from a starting point A, error and sin, to a destination point B, truth and virtue. Departing from the postulate, developed by cognitive semantics, that conceptual metaphors tend to be systematic and coherent, we will connect three processes of conceptual trasformation in Late Antiquity which have apparently no mutual relation. Only in the frame of the conversion image their internal coherence appears as evident: the obligation to choose between different religious options, the construction of a symmetrical dualism between Good and Evil, and the revolutionary idea that the new is superior to the ancient. The analysis is exemplified with some texts from Christian apologists and their pagan counterparts, specially those belonging to the protreptic genre.
Keywords: conversion; apologetics; protreptic genre; cognitive semantics; Christianity and Greek thought